2003
DOI: 10.1002/j.0022-0337.2003.67.1.tb03616.x
|View full text |Cite
|
Sign up to set email alerts
|

Issues Regarding Practical Validity and Gender Bias of the Perceptual Abilities Test (PAT)

Abstract: A brief history of the Dental Admission Test is provided, with emphasis on the development and utilization of the Perceptual Abilities Test (PAT). Concerns regarding the predictive utility of the PAT are discussed, and alternative approaches to assessing perceptual and motor skills are examined. To assess the predictive validity of the PAT, scores were collected for 492 students who graduated from the University of Oklahoma College of Dentistry over a ten-year period. Scores were compared to Preclinical Operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
34
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 19 publications
3
34
0
Order By: Relevance
“…There is also substantial evidence that studying dentistry significantly improves manual skills (Luck, Reitemeier, & Scheuch, ). This idea is consistent with studies that reported that the relationship between PAT and dental students' preclinical and clinical performance diminished with years of dental practice (Coy et al, ; Poole, Catano, & Cunningham, ). It should be noted, however, that the above studies investigated the relationship between spatial ability and dental performance that is primarily related to manual dexterity.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…There is also substantial evidence that studying dentistry significantly improves manual skills (Luck, Reitemeier, & Scheuch, ). This idea is consistent with studies that reported that the relationship between PAT and dental students' preclinical and clinical performance diminished with years of dental practice (Coy et al, ; Poole, Catano, & Cunningham, ). It should be noted, however, that the above studies investigated the relationship between spatial ability and dental performance that is primarily related to manual dexterity.…”
Section: Discussionsupporting
confidence: 89%
“…The results from the subsequent research investigating predictive validity of PAT, however, were not consistent. Although a few studies (e.g., Bellanti, Mayberry, & Tira, ; Gray & Deem, ) reported high correlation between PAT and preclinical grades in first‐year operative dentistry classes, a number of other studies found only weak to moderate correlations, suggesting that performance on PAT might not be a strong predictor of preclinical and clinical dental performance (Coy, McDougall, & Sneed, ; Curtis, Lind, Plesh, & Finzen, ; Hegarty, Keehner, Khooshabeh, & Montello, ; Oudshoorn, ; Ranney, Wilson, & Bennett, ; Sandow, Jones, Peek, Courts, & Watson, ). Moreover, Walcott, Knight, and Charlick () reported that PAT failed to significantly predict individual psychomotor performance on the first‐year operative dentistry exercises.…”
mentioning
confidence: 99%
“…This conclusion is also corroborated by a study of dental students who underwent a perceptual ability test that required participants to draw cross‐section cuts of teeth using pencil and paper. The study also required the students to develop spatial mental models of the 3D structure of teeth (Coy et al, ; Gansky et al, ). As a result, the students improved their ability to maintain and manipulate mental representations of dental structures, thus increasing their ability to visualize new spatial transformations in interventions in these teeth (Hegarty et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of research in this field concentrates on how dental admission tests (perceptual aptitude test, manual dexterity test, etc) can predict students’ performance in both preclinical and clinical courses in dental school. 1 , 4 , 13 , 16 However, studies correlating didactic scores to psychomotor performance, which was the focus of this study, are scarce. There is a need to further test such association in an attempt to further improve the educational experience in dental schools, and to develop new techniques of incorporating general and specific didactic dental knowledge toward acquiring and improving different psychomotor skills required for different dental specialties.…”
Section: Discussionmentioning
confidence: 99%